Determinan Persepsi Mengenai Etika Atas Penggelapan Pajak (Tax Evasion)(Studi Pada Mahasiswa Progam Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta) - Purnawati, Wahyu Hening Ririn, Dra. Mujiyati, M.Si (2017)
This research aimed to obtain emprical evidence about the effect of use of fairness, taxation system, discrimination, quality of tax service, and tax audit on the student perceptions about the ethics of tax evasion. This study was a quantitative research using primary data obtained from questionnaire and measured with likert scale. The method of selecting the sample in this study using convenience sampling. One hundred of the students majoring in accounting Faculty Economics and Business Muhammadiyah University of Surakarta were selected as the sample. The data were analyzed by using multiple linier regression analysis supported by SPSS. The result of this study shows that the fairness, taxation system, and tax audit does not significant the ethical perception towards tax evasion. Discrimination and quality of tax service has significant the ethical perception towards tax evasion. Keyword: fairness, taxation system, discrimination, quality of tax service, tax audit, perceptions about the ethics of tax evasion.